Integrating case-based learning with curriculum-based ideological and political education: enhancing undergraduate otolaryngology education - Shen, Yang; Zhang, Shuqing; Chang, Guanglei (Frontiers in Education, 2025)
The aim of this study was to explore the impact and practical value of combining case-based teaching with curriculum-based ideological and political education (CIPE) in undergraduate Otolaryngology theoretical courses by evaluations of the theoretical test, teaching satisfaction, and the integration of ideological and political education. In this randomized controlled trial, 366 fourth-year medical undergraduates were assigned to either an observation group, which received a semester of case-based CIPE in Otolaryngology, or a control group, which received traditional teaching methods focused on foundational theoretical knowledge. The final theoretical exam score and the process evaluation score, as well as the questionnaire on CIPE were collected. Data were analyzed using SPSS 24.0 statistical software. An independent sample T-test, the corrected χ2 test, and the non-parametric rank-sum test were used for statistical comparisons between the groups. The performance of students in the observation group was significantly higher than that of the control group. The overall satisfaction rate with the theory class was also significantly higher, and most students in the observation group had a strong recognition of the importance, specific connotation, training objectives, and methods of integrating ideological and political content. This study indicates that integrating case-based teaching with ideological and political education, to a large extent, improves students’ mastery of professional theory, stimulates proactive thinking, establishes correct professional values, and boosts their sense of professional pride and confidence. It is worth continuously practicing and exploring in our teaching activities.